Comparison of human ventral frontal cortex areas for cognitive control and language with areas in monkey frontal cortex - Neubert, F; Mars, R; Thomas, A; Sallet, J; Rushworth, M (Cell Press, 2014)
Human ventrolateral frontal cortex (vlFC) is identified with cognitive processes such as language and cognitive flexibility. The relationship between it and the vlFC of other primates has therefore been the subject of particular speculation. We used a combination of structural and functional neuroimaging methods to identify key components of human vlFC. We compared how vlFC areas interacted with other brain areas in 25 humans and 25 macaques using the same methods. We identified a core set of 11 vlFC components that interacted in similar ways with similar distributed circuits in both species and, in addition, one distinctively human component in ventrolateral frontal pole. Fundamental differences in interactions with posterior auditory association areas in the two species were also present-these were ubiquitous throughout posterior human vlFC but channeled to different frontal regions in monkeys. Finally, there were some differences in interregional interactions within vlFC in the two species.